Método y compulsa de fuentes en Carlos Araníbar Zerpa (1928-2016) - Huaraj Acuña, Juan Carlos (2025)
This text has two purposes. The first, to briefly reflect on the teacher Carlos Araníbar and some generalities about the generation of 50’. The second, on his method of verification and analysis of the sources, consequently, elucidate the validity and contemporaneity of the methodological guidelines that the aforementioned teacher exposed and suggested in different of his writings and interviews throughout his fruitful academic life.